A prelude to statistics arising from optimal transport theory - Hung T. Nguyen (Asian Journal of Economics and Banking (AJEB), 2023)
Purpose - This paper aims to offer a tutorial/introduction to new statistics arising from the theory of optimal transport to empirical researchers in econometrics and machine learning. Design/methodology/approach - Presenting in a tutorial/survey lecture style to help practitioners with the theoretical material. Findings - The tutorial survey of some main statistical tools (arising from optimal transport theory) should help practitioners to understand the theoretical background in order to conduct empirical research meaningfully. Originality/value - This study is an original presentation useful for new comers to the field.
Keywords: 330; Multivariate quantiles; Optimal transport; Partial identification; Random sets; Wasserstein metrics